The impact of government expenditure on economic growth in South Africa: A VECM Approach - Nhlangwini, P.; Tleane, K. (IPADA, 2019)
Economists hold opposing views as to whether government expenditure is an effective way to stimulate the economy or not, while economic theory as well does not generate strong conclusions on the same issue. It is against this background that this paper aims to explore whether there exists a relationship between government expenditure and economic growth in South Africa. This paper employs the Johansen Cointegration analysis and Vector Error Correction Model on time series for the period 1997-2017 to examine the relationship. The paper further employs the Impulse Response Function to check for possible shocks among the variables. The empirical results strongly support the Keynesian view and the hypothesis that government expenditure is beneficial to economic growth in South Africa. Results revealed a long-run and short-run relationship amongst the variables. Moreover, the classification of government expenditure indicates that social infrastructure significantly contributes to a higher economic growth in the short-run then contract negatively in the long-run. However, economic infrastructure has no impact towards economic growth. The findings may provide an overview of policy suggestions to improve the effects that government expenditure has on economic growth. Keywords: Government expenditure, Economic growth, VECM, Generalised impulse response function
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Government expenditure; Economic growth; VECM; Generalised impulse response function; Tax and expenditure limitations -- Law and legislation; Economic growth